Politiques de l’amour et du sexe dans la Chine de la « révolution sexuelle » - Jean-Baptiste Pettier (Genre, Sexualité et Société)
This article questions the relevance of the use of the expression “sexual revolution” when talking about the transformations of the sexual practices of the young Chinese girls and boys who grew up with the economic reforms initiated in the 1980s. The article also suggests an historical perspective for the changes in the social monitoring of sexuality in China during the twentieth century. Far from being a “liberation” against the repression of sexuality by the state, the strong re-sexuation of the present Chinese social world is actually right in line with the liberal economic opening and the competition for individual success it create.